2008
DOI: 10.1111/j.1551-2916.2008.02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Treatment of Si3N4 Filler Particles for the Improvement of Si3N4filler/Si–C–Nmatrix Particulate‐Reinforced Composites

Abstract: The surface of Si3N4 filler particles was modified by heat treatments before the onset of the precursor impregnation and pyrolysis process. The strength, Young's modulus, and hardness of Si3N4filler/Si–C–Nmatrix particulate‐reinforced composites (PRC) were improved up to 50%, 60%, and 71%, respectively, by the treatment. Si was formed at the surface of the Si3N4 filler particles by the treatment, which induced a strong bonding between the filler and the Si–C–N matrix during pyrolysis by a carbothermal reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…SiC is thermally stable at 2000°C and SiO 2 formed on SiC was mostly removed before the PIP process by the pretreatment at 1750°C in Ar 7 . Accordingly, the weight loss of the PRC above 1400°C in Ar (5% at 1800°C, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…SiC is thermally stable at 2000°C and SiO 2 formed on SiC was mostly removed before the PIP process by the pretreatment at 1750°C in Ar 7 . Accordingly, the weight loss of the PRC above 1400°C in Ar (5% at 1800°C, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2a indicated that the enlargement of pores at the surface of the 1350‐6cycle PRC after the heating at 1500°C in Ar (Figs. 3a and b) was caused by the decomposition of the Si–C–N matrix 7 . The specimen shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations